2022
DOI: 10.1155/2022/2126518
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin Price Forecasting: An Integrated Approach Using Hybrid LSTM-ELM Models

Abstract: In recent years, digital currencies have flourished on a considerable scale, and the markets of digital currencies have generated a nonnegligible impact on the whole financial system. Under this background, the accurate prediction of cryptocurrency prices could be a prerequisite for managing the risk of both cryptocurrency markets and financial systems. Considering the multiscale attributes of cryptocurrency price, we match the different machine learning algorithms to corresponding multiscale components and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The study made the model more productive in obtaining accurate results for each item in the product life cycle. Meanwhile, [9] applied ELM integrated with LSTM to Bitcoin price forecasting. Their study matches the different machine learning algorithms to corresponding multiscale components and constructs the ensemble prediction models based on machine learning and multiscale analysis.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The study made the model more productive in obtaining accurate results for each item in the product life cycle. Meanwhile, [9] applied ELM integrated with LSTM to Bitcoin price forecasting. Their study matches the different machine learning algorithms to corresponding multiscale components and constructs the ensemble prediction models based on machine learning and multiscale analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Their study matches the different machine learning algorithms to corresponding multiscale components and constructs the ensemble prediction models based on machine learning and multiscale analysis. The results showed that the ensemble models can achieve a prediction accuracy of 95.12% with enhanced performance than the benchmark models [9]. Moreover, Cholid and Aly [10] forecasted spiral and leaf spring products for fourwheeled vehicles using the Artificial Neural Network Backpropagation method.…”
Section: Related Workmentioning
confidence: 99%